Protective Effect of Chlorogenic Acid and Its Analogues on Lead-Induced Developmental Neurotoxicity Through Modulating Oxidative Stress and Autophagy - Ji, Xiuna; Wang, Baokun; Paudel, Yam Nath; Li, Zhihui; Zhang, Shanshan; Mou, Lei; Liu, Kechun; Jin, Meng (Frontiers in Molecular Biosciences, 2021)
Lead (Pb) is among the deleterious heavy metal and has caused global health concern due to its tendency to cause detrimental effect on the development of central nervous system (CNS). Despite of being a serious health concern, treatment of Pb poisoning is not yet available reflecting the pressing need of compounds that can relieve Pb-induced toxicity, especially neurotoxicity. In the quest of exploring therapeutic strategies against Pb induced neurotoxicity, compounds from natural resources has gained increased attention. Chlorogenic acid (CGA) and its analogues neochlorogenic acid (NCGA), cryptochlorogenic acid (CCGA) are the important phenolic compounds widely distributed in plants. Herein, utilizing zebrafish as a model organism we modeled Pb induced developmental neurotoxicity and investigated the protective effect of CGA, NCGA and CCGA co-treatment. In zebrafish, Pb exposure (1000 µg/L) for 5 days causes developmental malformation, loss of dopaminergic (DA) neurons and brain vasculature, as well as disrupted neurons differentiation in the CNS. Additionally, Pb-treated zebrafish exhibit abnormal locomotion. Notably, co-treatment with CGA (100 µM), NCGA (100 µM), and CCGA (50 µM), alleviate these developmental malformation and neurotoxicity induced by Pb. Further underlying mechanism investigation revealed that these dietary phenolic acid compounds may ameliorate Pb induced oxidative stress and autophagy in zebrafish, therefore alleviating Pb-induced developmental neurotoxicity. In general, our study indicates that CGA, NCGA and CCGA could be promising agents for treating neurotoxicity induced by Pb and CCGA shows the strongest detoxifying activity.